An Evaluation of the Impact of a Nurse-Led Program on Knowledge and Practices Related to Needle Stick Injury Prevention Among 2nd Year B.Sc. Nursing Students at the College of Nursing, PT. B.D. Sharma PGIMS, Rohtak - Adarsh; Rajpati; Kavita Choudhary (International Journal of Evidence Based Nursing And Practices, 2025)
Healthcare workers and nursing students frequently face accidental occupational exposures while caring for patients, with needle stick injuries being the most common form of exposure in healthcare settings. These injuries pose a significant risk of infections. This study aimed to evaluate the awareness and practices related to the prevention of needle stick injuries among second-year B.Sc. Nursing students, assess the effectiveness of a nurse-led intervention in enhancing their knowledge and practices, and explore the relationship between pre-test knowledge and practice scores and certain demographic factors. A quantitative, pre-experimental design using a one-group pre-test and post-test approach was implemented, involving 150 second-year B.Sc. Nursing students selected through purposive sampling. Data were gathered using a self-designed questionnaire and a practice checklist. The findings revealed that, in the pre-test, 17% of students had insufficient knowledge, 81% had moderate knowledge, and only 2% demonstrated adequate knowledge. Following the intervention, 90% of students achieved adequate knowledge, and only 10% had moderate knowledge. In terms of practice, 32% of students had unsatisfactory practices in the pre-test, which improved significantly after the intervention, with 14% demonstrating satisfactory practices. The knowledge score increased from a pre-test mean of 14.04 (±3.35) to a post-test mean of 24.08 (±2.33), and the practice score rose from 7.29 (±1.56) to 8.93 (±1.37), both showing significant improvements (t-values of 39.407 and 17.313, respectively). Additionally, a significant association was found between pre-test knowledge scores and vaccination status (χ²=7.187, df=2). However, no demographic variable was significantly associated with pre-test practice scores. The findings indicate that the nurse-led program was highly effective in enhancing both the knowledge and practices of nursing students regarding needle stick injury prevention and post-exposure prophylaxis. This highlights the significance of such programs in enhancing workplace safety practices.
Keywords: Needle stick injury; Post exposure prophylaxis; knowledge and practice; nurse led programme